Experimental study and thermodynamic modeling of the Al–Co–Cr–Ni system. Issue 5 (21st September 2015) - Gheno, Thomas; Liu, Xuan L; Lindwall, Greta; Liu, Zi-Kui; Gleeson, Brian
Abstract: A thermodynamic database for the Al–Co–Cr–Ni system is built via the Calphad method by extrapolating re-assessed ternary subsystems. A minimum number of quaternary parameters are included, which are optimized using experimental phase equilibrium data obtained by electron probe micro-analysis and x-ray diffraction analysis of NiCoCrAlY alloys spanning a wide compositional range, after annealing at 900 °C, 1100 °C and 1200 °C, and water quenching. These temperatures are relevant to oxidation and corrosion resistant MCrAlY coatings, where M corresponds to some combination of nickel and cobalt. Comparisons of calculated and measured phase compositions show excellent agreement for the β – γ equilibrium, and good agreement for three-phase β – γ – σ and β – γ – α equilibria. An extensive comparison with existing Ni-base databases (TCNI6, TTNI8, NIST) is presented in terms of phase compositions.